Evaluation of Post-operative Complications following Thyroid Surgery - Talukder, Debesh Chandra; Sarker, Satinath Chandra; Ahasan, Syed Ali; Haque, Muhammad Mozammal; Arefin, Mostafa Kamal; Musabbir, Nadira; Rahman, Chowdhury Md Mushfiqur (Journal of Dhaka Medical College, 2020)
Objectives: This study evaluates the incidence, Frequency and risk factors of complications in patients submitted to thyroidectomy for various benign and malignant lesion and to corroborate the results in relation to the extent of surgery in a Tertiary level hospital. Study design : An analytical study of 100 consecutive patients who underwent thyroidectomy for benign and malignant thyroid lesion. Material s and methods: The study was carried out at Department of ENT and Head-Neck surgery in Dhaka Medical College Hospital over a period of 1.5 years from January 2017 to June 2018. Data were collected from 100 patients who underwent thyroidectomies for various thyroid diseases at this center. Results: There were 80 females (80%) and 20 males (20%) with female-to-male ratio of 4:1, and The age range of the patients were 15 to 80 years, the mean age was 39.29 years. Preoperative diagnosis of benign and malignant pathologies was made in 86% and 14% cases respectively. Most common pathological diagnosis was colloid goiter 46%,nodular of cases, whereas papillary carcinoma accounting for 11% was the commonest malignant lesion .The types of thyroid operations done were as follows (Table-II). The commonest operation performed was hemithyroidectomy (45%). The overall postoperative complication rate was 17%.Temporary and permanent RLNI occurred in 3% and 2% respectively. The less common complications were wound hematoma, seroma formation, and superior laryngeal nerve injury. There was no mortality observed in this study. Conclusion: In conclusion, extent of resection, surgical technique and thyroid pathologic condition had a greater impact on the rates of postoperative complications. By developing understanding of the anatomy and the ways to prevent each complication, the surgeon can minimize each patient’s risk and can handle complications expediently and avoid worse consequence. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 108-113